Identification of specific reference gene for normalization of RT-qPCR data in rhythmic gene expression studies of the effect of developmental hormone antagonist in postembryonic development in Bombyx mori - Dalai, Minurani; Jagota, Anita (Frontiers in Insect Science, 2024)
Bombyx mori is a lepidopteran holometabolous insect with distinct developmental stages: egg, larvae, pupae, and adult. The lepidopteran insect undergoes major modifications in the CNS so as to adapt to the lifestyle of these distinct stages with specific habitats and functions from voraciously feeding larval stages to flying reproductive adults via dormant pupal stages. Such transitions are linked to transcriptional, epigenetic, and translational complexities. Therefore, to study rhythmic gene expression in CNS of various developmental stages and the effects of antagonists on developmental hormones requires a very stable Reference gene (RG).To facilitate rhythmic gene expression studies using RT-qPCR in B. mori and the effect of developmental hormone juvenile hormone (JH) and 20-hydroxy ecdysone hormone (20 HE) antagonists precocene 1 and testosterone respectively were used. Eight candidate RGs such as Translational initiation factor 3 subunit 4 (TI3S4), Translational initiation factor 3 subunit 5 (TI3S5), Ribosomal protein subunit 7 (RPs7), TATA-binding protein association factor (TAF13), Translational initiation factor 4 A (TI4A), Ribosomal protein (RPL32), Elongation factor 1 (EF1), and Arginine kinase (AK) were assessed in the central nervous system (CNS) of B. mori. The postembryonic developmental (PED) stages used were the fifth late larval instar, early pupa, mid pupa, late pupa, and adult. The assessments were done at four different time points (Zeitgeberstime (ZT)) 0, 6, 12, and 18 to find stability towards 24h rhythmic expression.RefFinder, geNorm, and Ct value analysis were performed. RefFinder, geNORM studies suggested stability order as TI3S4>TI3S5>RPs7 but Ct value evaluation showed stability order as TI3S5>TI3S4>RPs7.We therefore demonstrated that TI3S4, TI3S5, and RPs7 can be used as RG in various PED stages in CNS of B. mori (Strain: CB-hybrid, PM×CSR2) towards studies with effects of JH and 20 HE antagonists.